2011
DOI: 10.1111/j.1365-2699.2011.02494.x
|View full text |Cite
|
Sign up to set email alerts
|

The Linnean shortfall in oceanic island biogeography: a case study in the Azores

Abstract: Isolated oceanic archipelagos are natural laboratories of evolution, ideally suited for in situ studies of speciation processes, and the recent availability of checklist data for many archipelagos worldwide (e.g. Izquierdo et al., 2004;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
89
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 47 publications
19
89
2
Order By: Relevance
“…This results parallels previous observations of the sharing of alleles among Macaronesian and Mediterranean accessions in the mosses Leucodon sciuroides (Stech et al, 2011), Grimmia montana and Kindbergia praelonga (Hedenäs, 2010). Altogether, these observations weaken the idea, that the low rates of endemism observed in the Macaronesian bryophyte flora might, as has been for instance evoked in the Azorean angiosperm flora (Schaefer et al, 2011), be explained by the Linnean shortfall. The absence of genetic differentiation between sympatric R. riparioides and the Canarian endemic G. torrenticola further suggests that, despite a strikingly different morphology, the two species are not reproductively isolated, and should hence be reduced into synonymy (Werner et al, 2007).…”
Section: Tablesupporting
confidence: 90%
See 1 more Smart Citation
“…This results parallels previous observations of the sharing of alleles among Macaronesian and Mediterranean accessions in the mosses Leucodon sciuroides (Stech et al, 2011), Grimmia montana and Kindbergia praelonga (Hedenäs, 2010). Altogether, these observations weaken the idea, that the low rates of endemism observed in the Macaronesian bryophyte flora might, as has been for instance evoked in the Azorean angiosperm flora (Schaefer et al, 2011), be explained by the Linnean shortfall. The absence of genetic differentiation between sympatric R. riparioides and the Canarian endemic G. torrenticola further suggests that, despite a strikingly different morphology, the two species are not reproductively isolated, and should hence be reduced into synonymy (Werner et al, 2007).…”
Section: Tablesupporting
confidence: 90%
“…For example, studies based on the analysis of distribution data from checklists found that the flora of the Azores differs from other island floras in the exceptionally low number of radiations and the low number of single-island endemics (Carine and Schaefer, 2010). Recognition as distinct taxa of the genetically distinct entities discovered by molecular analyses drastically change the diversity patterns and make them more similar to those of other Atlantic archipelagos, highlighting that current knowledge of endemic diversity on oceanic islands may be far from complete (Schaefer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of Silva et al (2011) it was identified a high degree of differentiation and restricted gene flow between populations, which contradicts the accepted theories for the Azorean plant diversity with low number of radiations and low number of single-island endemics and also contradicts the life traits of this species that favours the long distance dispersal, colonization and gene flow exchange (Carine and Schaefer, 2010;Rumeu et al, 2011a;Schaefer et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…This taxon formed the least distinct of the Azorean Leontodon based on the molecular analysis results although notably Terceira accessions clustered together with low (61−63%; MP) to high (84−95%; ML) support in the nuclear and cp trees, highlighting the distinctiveness of plants from the island, a pattern also found in other angiosperm groups (Schaefer et al 2011b;Silva et al 2011). In the discriminant morphological analysis, the central group accessions formed a separate group, and the ANOVA indicated that the central group accessions were significantly different for most of the analysed traits.…”
Section: Discussionmentioning
confidence: 97%